Світовий досвід функціонування таргетинг-центрів в контексті забезпечення митної безпеки - Туржанський, В. А.; Несторишен, І. В.; Туржанский, В. А.; Несторишен, И. В.; Turzhanskyi, V.; Nestoryshen, I. (ЦНТУ, 2018)
У статті досліджено зарубіжний досвід функціонування центрів таргетингу при здійсненні митного контролю з метою забезпечення митної безпеки. Визначено сутність таргетингу, основні типи завдань таргетинг-центрів та можливість їх впровадження в діяльність ДФС України. Встановлено, що таргетинг є сучасним інструментом митного контролю, який створює передумови для оперативного опрацювання великих об’ємів інформації щодо вантажів, пасажирів та транспортних засобів, які переміщуються через митні кордони країн, а також дозволяє відійти від практики інтуїтивного вибіркового обрання об’єкта поглибленого огляду. В статье исследован зарубежный опыт функционирования центров таргетинга при осуществлении таможенного контроля с целью обеспечения таможенной безопасности. Определена сущность таргетинга, основные типы задач таргетинг-центров и возможность их внедрения в деятельность ДФС Украины. Установлено, что таргетинг является современным инструментом таможенного контроля, создает предпосылки для оперативной обработки больших объемов информации по грузам, пассажиров и транспортных средств, перемещаемых через таможенные границы стран, а также позволяет отойти от практики интуитивного выборочного избрания объекта углубленного осмотра. In the conditions of the formation of an integrated system for the implementation of the state customs business, the issue of securing the implementation of international trade becomes especially urgent. Realization of this task is possible only with the use of modern customs control instruments and the formation of an adequate customs information environment through the use of prior information. At the same time, targeting, based on the use of risk profiles and other information and enforcement measures, for the selection of passengers, vehicles and goods requiring additional inspection, is increasingly popular. The article investigates the foreign experience of the operation of targeting centers in the implementation of customs control in order to ensure customs security. The essence of targeting, main types of tasks of the target-centers and the possibility of their introduction into the activity of the State fiscal service of Ukraine are determined. It has been established that targeting is a modern tool for customs control, which creates the preconditions for the rapid processing of large volumes of information on goods, passengers and vehicles moving through the customs borders of the countries, and also allows to depart from the practice of intuitive selective selection of in-depth inspection object. Targeting centers provide better risk assessment capabilities across the entire range of border and customs functions, management and integration of information databases, coordination of intelligence and operational activities, and contributes to the overall effective implementation of the concept of integrated border management. The reasons for their creation in each country are different; they do not have a clear set of functions. Targeting Centers have made it possible to improve: management and data synthesis; application of the approach to the assessment and definition of objects for verification, which is coordinated at the national level; coordination of activities for the collection of operational data and operational activities; as well as the possibility of integrated border risk management across the entire border sector. The authors study the peculiarities of the operation of targeting centers in Canada, Finland, New Zealand, Germany, USA, China, Brazil and Australia. Overall, the analysis of the functioning of the targeting centers has led to the conclusion that they provide countries with additional benefits by improving the management and synthesis of information; more effective use of the approach to risk assessment and definition of facilities for national-level coordinated verification; the expansion of the link between activity for the collection of operational data and operational activities; and a more coordinated approach to border risks and more effective achievement of national boundary management objectives. Thus, the functioning of targeting centers intensifies the effect of interagency interaction, in particular, in the implementation of the state customs business and raises national security to a much higher level of protection of the economic interests of the country. It is established that the introduction of the latest information risk-oriented tools taking into account the foreign experience of the operation of the targeting centers can bring Ukraine closer to the best practice in customs procedures in the context of their simplification and customs security.
Мировой опыт функционирования центров таргетинга в контексте обеспечения таможенной безопасности
Worldwide Experience of Targeting Centers in the Context of Customs Security
Keywords: таргетинг; митна безпека; система аналізу та управління митними ризиками; таможенная безопасность; система анализа и управления таможенными рисками; targeting; customs security; system of analysis and customs risk management